Advances in PD-1 and CTLA-4 dual-target immunotherapy for ovarian cancer - Li, Dong-Mei; Pei, Kai-Ge; Yu, Xiu-Zhang; Qie, Ming-Rong; Zhong, Lan; Song, Liang (Frontiers in Immunology, 2025)
Ovarian cancer(OC) remains a major threat to women’s health, ranking among the top gynecologic malignancies in both incidence and mortality. Current clinical management continues to center on cytoreductive surgery combined with a multidisciplinary approach incorporating chemotherapy, targeted therapy, and immunotherapy. Notably, while single-agent immunotherapy has demonstrated limited efficacy in recurrent OC, recent breakthrough advances in dual-target immunotherapy have brought new hope for advanced-stage and recurrent patients. Clinical evidence indicates that programmed death-1/cytotoxic T-lymphocyte-associated protein 4 (PD-1/CTLA-4) dual immune checkpoint blockade strategies (e.g., durvalumab plus tremelimumab, nivolumab plus ipilimumab) exhibit differential therapeutic effects: durable treatment responses have been observed in recurrent/platinum-resistant advanced OC, while neoadjuvant applications have significantly improved complete resection rates. However, these therapeutic benefits demonstrate marked heterogeneity across different histological subtypes. The review of current research reveals several critical issues: first, the safety profile of dual immunotherapy requires further characterization; second, data on first-line treatment for advanced OC remain scarce; and third, optimal treatment strategies have yet to be established. Nevertheless, multiple ongoing clinical trials are paving the way for future research directions, including optimization of combination regimens and exploration of predictive biomarkers. In conclusion, despite existing challenges, dual-target immunotherapy has demonstrated clinically meaningful benefits, offering new therapeutic options for advanced and recurrent OC patients and heralding a new era of combination immunotherapy in OC treatment. Future large-scale clinical studies are warranted to further validate efficacy and establish individualized precision treatment strategies.